2014
DOI: 10.1016/j.foodchem.2013.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and instrumental analysis of medium and long shelf-life Charentais cantaloupe melons (Cucumis melo L.) harvested at different maturities

Abstract: HighlightsFlavour of medium and long shelf-life Charentais cantaloupe melons was compared.Volatile and semi-volatile profiles were correlated with sensory data using multifactorial analysis.Maturity at harvest has a significant impact on the flavour of medium-shelf life fruit.Maturity at harvest had much less impact on a long shelf-life genotype.Esters and sulphur-compounds were more abundant in mature medium shelf-life fruit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 32 publications
10
33
1
Order By: Relevance
“…HDMF was first reported as a product of the Maillard reaction (Hodge et al, 1963) and was subsequently isolated from different fruits, including pineapple, strawberry, and tomato (Rodin et al, 1965;Buttery et al, 2001;Ubeda et al, 2012;Schwab, 2013). HDMF exhibits a caramel-like aroma similar to that of its structural homologs HMF and EHMF, which were identified in tomato and melon fruits (Lignou et al, 2014), respectively; however, the biogenetic pathways of these compounds remain unknown. In this study, we found that UGT71K3a and its allelic protein UGT71K3b could accept HDMF as a substrate and form HDMFglucoside (Fig.…”
Section: Glucosylation Of Volatile Metabolites In Strawberrymentioning
confidence: 99%
“…HDMF was first reported as a product of the Maillard reaction (Hodge et al, 1963) and was subsequently isolated from different fruits, including pineapple, strawberry, and tomato (Rodin et al, 1965;Buttery et al, 2001;Ubeda et al, 2012;Schwab, 2013). HDMF exhibits a caramel-like aroma similar to that of its structural homologs HMF and EHMF, which were identified in tomato and melon fruits (Lignou et al, 2014), respectively; however, the biogenetic pathways of these compounds remain unknown. In this study, we found that UGT71K3a and its allelic protein UGT71K3b could accept HDMF as a substrate and form HDMFglucoside (Fig.…”
Section: Glucosylation Of Volatile Metabolites In Strawberrymentioning
confidence: 99%
“…Until now, around 300 volatile compounds have been identified in muskmelon and watermelon samples (Beaulieu & Grimm, 2001;Beaulieu & Lancaster, 2007;Beaulieu & Lea, 2006;Beaulieu, 2006aBeaulieu, , 2006bHomatidou, Karvouni, Dourtoglou, & Poulos, 1992;Itrat, 2006;Jordán, Shaw, & Goodner, 2001;Kourkoutas, Elmore, & Mottram, 2006;Liu et al, 2012;Obando-Ulloa & Moreno, 2008;Obando-Ulloa & Ruiz, 2010;Perry, Wang, & Lin, 2009;Saftner, Abbott, Lester, & Vinyard, 2006;Verzera, Dima, Tripodi, & Ziino, 2011). Due to the important role of volatile components in organoleptic quality of foods and beverages, these compounds have been widely studied and analytical methodologies for their determination in fruit matrices are continuously being developed, including both GC (Beaulieu, Ingram, Lea, & Bett-Garber, 2004;Beaulieu & Lancaster, 2007;Beaulieu & Lea, 2006;Gonda et al, 2010;Kemp, 1975;Kourkoutas et al, 2006;Liu et al, 2012) and GC-O (Jordán et al, 2001;Lignou, Parker, Baxter, & Mottram, 2014) …”
Section: Introductionmentioning
confidence: 99%
“…Cantaloupe is available all year round in Thailand; however, its shelf life is limited to approximately 15 days. This results in large losses of the crop and value (Laur and Tian, 2011;Lignou et al, 2014). The manufacture of jam is very typical in fruit preservation and could be applied to extend the shelf life of cantaloupe.…”
Section: Introductionmentioning
confidence: 99%